Pengaruh Net Profit Margin, Current Ratio dan Debt to Equity Terhadap Pertumbuhan Laba - Ardiansyah, Rizki (COMPETITIVE, 2023)
The purpose of this study is to find out the effect of Net Profit Margin, Current Ratio and Debt to Equity on Profit Growth in State-Owned Enterprises (BUMN) for the 2016-2020 period. The independent variables used in this research are Net Profit Margin, Current Ratio and Debt to Equity and Profit Growth of the dependent variable.               The method in this study is a quantitative method with an associative approach. The population in this study were all State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, totaling 20 companies. The sample in this study used a purposive sampling technique so that there were 7 companies that met the criteria. The data collection technique used is secondary data or secondary sources. The data analysis technique used is quantitative with classical assumption test analysis, multiple regression test, hypothesis testing and determinant coefficient test. The software used for data processing is SPSS 25 software.               The results of this study are Net Profit Margin partially has no effect on profit growth, Current Ratio partially does not affect profit growth and debt to equity partially has a negative and significant effect on profit growth. And Net Profit Margin, Current Ratio and Debt to Equity simultaneously have no effect on profit growth in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange.